کریگ کنسیڈائن کی کتاب People of The Book: Prophet Muhammad Encounters With The Christians کا تجزیاتی مطالعہ: (An analytical study of Craig Considine’s book "People of the Book: Prophet Muhammad Encounters With the Christians) - Hafiz Abdul Haseeb; Dr. Mahmood Ahmad( Corresponding Author) (International Research Journal of Arabic and Islamic Studies, 2024)
This article is based on a new book by Craig Considine, "People of the Book: Prophet Muhammad's Encounters with Christians." It was published in 2021 by Hurst & Company, 191 pages including six chapters. The book describes the encounters Prophet Muhammad had with Christians, the interactions of both sides and the importance of cross-fertilization of ideas, religious freedom and mutual respect. Considine's attempt to foster Christian-Muslim relations is rife with interpretations of Islam that question Islamic teachings and traditions. Though the book does interweave historical anecdotes with Qur'anic verses alongside prophetic traditions, its references have been subjective and selective, thus critically damaging. Using a historiographic approach, Considine studied events such as the migration to Abyssinia, the Constitution of Medina, and treaties with Christians. Although its references to Islamic and Christian texts are certainly extensive, the book has come under scrutiny for relying on secondary sources and less established traditions.